PENGATURAN KLAUSULA BAKU PADA JUAL BELI ONLINE - Ratihayu, Annisa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2024)
Abstract This research discusses the policy of standard clauses in the Consumer Protection Act (UUPK) in relation to online buying and selling activities, especially through e-commerce. In the delivery of products purchased online, the phrase